PKM Pembuatan dan Pengelolaan Website Badan Usaha Milik Desa Bersama Sabana Kamek LKD Kamang Magek Kabupaten Agam - Fitra, Halkadri; Satrianto, Alpon; Andi Mesta, Hendri (Universitas Negeri Padang, 2024)
The training program on Website Creation and Management for Sabana Kamek Village-Owned Enterprise (BUMDesma) under LKD Kamang Magek, Kabupaten Agam, aims to enhance human resource capacity in managing businesses through digital technology. This training is designed to provide a basic understanding of the importance of information technology in supporting transparency, efficiency, and the marketing of BUMDesma's products and services to a broader audience. During the program, participants were introduced to fundamental concepts of website management, technical steps in website creation, and strategies for utilizing websites to support branding and digital marketing. The training employed a combination of theoretical and practical approaches, enabling participants not only to grasp the concepts but also to independently implement the acquired skills. The outcomes of the training indicate that participants successfully created and managed simple websites to support BUMDesma operations. The positive impact of this program is expected to expand the marketing reach of BUMDesma’s products, enhance business competitiveness, and strengthen information transparency for the community and stakeholders. As a follow-up, continuous assistance and advanced training will be necessary to ensure the sustainability of information technology utilization in BUMDesma management.